Rainfall Event Analysis for Urban Flooding Study Using Radar Rainfall Data. - Mahmmud, Rebar Muhammad Jaza (Sulaimani Journal for Pure and Applied Sciences, 2015)
Urban flooding is one of the most serious challenges facing urban areas and causes destruction of properties and major problems for people living in urban areas. It occurs in an urban area when intense convective rainfall happens that is higher than the capacity of the urban drainage system. Rainfall data can be recorded by radar and by rain gauge. It is essential for urban flooding studies to have access to high quality rainfall data in attempting to reduce and tackle this challenge. The main aim of this paper is to test the quality of radar data by means of rainfall event analysis. Radar data obtained from Yorkshire Water were analysed and compared to rain gauge data during selected rainfall events in a study area located in North Yorkshire in the UK. Rainfall intensity curves within 5 minute and one-hour intervals, cumulative rainfall depth curves and normalised bias were used as standard methods for comparison between radar and rain gauge data during the selected rainfall events. Available data were collected for June, July, and October 2008 and were recorded from Blackhill, Harrogate North, and Helmsley rain gauges, and radar data for these same locations were also collected. The results of this thesis show that certain errors might have an impact on radar data in terms of quality. Some such errors caused overestimation of radar rainfall data, such as anomalous propagation error and error related to thunderstorm. However, other errors, such as attenuation, caused underestimation in radar rainfall data.
Keywords: Rainfall event analysis; Urban flooding; Comparison of radar and rain gauge data; Quality of radar data Sources of error inradar and rain gauge data